Possibilidades para a utilização de biogás: um estudo teórico - Gomes, Leonardo Henrique Santos (2017)
This work aims to identify possibilities for biogas utilization through theoretical studies and legal observances. Thus, regulations, legislation applicable to the biogas energy utilization and work on the energy generation using biogas were analyzed. In the regulatory aspect, the work seeks to establish the necessary basis for using a biodigester according to the existing regulatory norms for its operation. In the legislative aspect, it was pointed out the main laws and obligations in force up to the date of the work so that the biogas production can be started, the possibility of producing and commercializing biomethane, which is the purified biogas, and the commercialization of the biogas was studied. Energy produced by the combustion of biogas in generators. From an environmental point of view, it is worth noting the feasibility of reducing environmental liabilities, generating renewable energy and using the energy potential of organic waste that sometimes does not have an environmentally adequate destination. As a result, regulated possibilities for biogas production and use were obtained.